ABOUT THE INCA OCCUPATION OF THE MALA VALLEY (CAÑETE, LIMA) - Tantaleán, Henry (2004)
We disscuse the two last prehispanic ocuppations in the lower Mala valley as a consequence our archaeological research developemented to the present. Specifically, we discusse the Inca Occupation as a dialectical process that supossed the confrontation of two societies: the local and the invaders in an area previously assumed as a “social vacuum” in the prehispanic central coast.